Complement is dispensable for neurodegeneration in Niemann-Pick disease type C - Lopez, Manuel E (BioMed Central, 2012)
BACKGROUND: The immune system has been implicated in neurodegeneration during development and disease. In various studies, the absence of complement (that is, C1q deficiency) impeded the elimination of apoptotic neurons, allowing survival. In the genetic lysosomal storage disease Niemann-Pick C (NPC), caused by loss of NPC1 function, the expression of complement system components, C1q especially, is elevated in degenerating brain regions of Npc1(-/-) mice. Here we test whether complement is mediating neurodegeneration in NPC disease. FINDINGS: In normal mature mice, C1q mRNA was found in neurons, particularly cerebellar Purkinje neurons (PNs). In Npc1(-/-) mice, C1q mRNA was additionally found in activated microglia, which accumulate during disease progression and PN loss. Interestingly, C1q was not enriched on or near degenerating neurons. Instead, C1q was concentrated in other brain regions, where it partially co-localized with a potential C1q inhibitor, chondroitin sulfate proteoglycan (CSPG). Genetic deletion of C1q, or of the downstream complement pathway component C3, did not significantly alter patterned neuron loss or disease progression. Deletion of other immune response factors, a Toll-like receptor, a matrix metalloprotease, or the apoptosis facilitator BIM, also failed to alter neuron loss. CONCLUSION: We conclude that complement is not involved in the death and clearance of neurons in NPC disease. This study supports a view of neuroinflammation as a secondary response with non-causal relationship to neuron injury in the disease. This disease model may prove useful for understanding the conditions in which complement and immunity do contribute to neurodegeneration in other disorders.